Ideological Representation in the Short Story Collection Corat-coret di Toilet by Eka Kurniawan: Gramsci's Hegemony Analysis - Anggraeni, Astri; Fatimah, Ade Fitria; Darmawan, Auranita Gibrani (Journal of Literary Prose and Society, 2025)
This article explores ideological representation in Eka Kurniawan’s short story collection Corat-coret di Toilet using Antonio Gramsci’s theory of hegemony. The study aims to examine how dominant and subaltern ideologies are contested and negotiated within the selected stories. Employing a qualitative descriptive method, the research focuses on four short stories that exhibit significant ideological formations: "Doodling in the Toilet," "The Beauty Who Can’t Go Out at Night," "Peter Pan," and "The Capture of the Little Bread Thief." The findings reveal the presence of dominant ideologies such as idealism, feudalism, and capitalism, while the subaltern ideologies attempting negotiation include democracy, humanism, liberalism, and nationalism. Each story presents ideological resistance, yet the talks ultimately fail due to the persistence of dominant power. In Gramscian terms, the hegemony depicted in these narratives aligns with minimal hegemony, where consensus between rulers and the ruled is absent. The study also concludes that Eka Kurniawan, as an organic intellectual, fails to create a transformative ideological shift. Instead, the stories illustrate ongoing struggles without resolution. This research contributes to the understanding of literature as a site of ideological conflict and suggests that future studies examine other dimensions of Gramsci’s hegemony within Indonesian literary texts.